Delivering food security without increasing pressure on land - Smith, Pete (Global food security, 2013)
The challenge of feeding 9 to 10 Billion people by 2050 may seem like a big enough challenge in itself, but we also need to achieve this feat whilst, at the same time, reducing adverse impacts of food production on a whole range of ecosystem services. One suggested response is “sustainable intensification” which entails delivering safer, nutritious food from the same area whilst maintaining ecosystem service provision. In this review, I examine sustainable intensification and consider alternatives such as management of food demand and waste reduction. I conclude that sustainable intensification has a role to play, but this must be accompanied by fundamental change in global food systems. ► Food production can increase by expanding agricultural area or increasing per-area productivity. ► Expanding agriculture into forests and natural areas is environmentally damaging. ► To meet future food demand per-area productivity must increase, through “sustainable intensification”. ► Sustainable intensification will be challenging, and will not be without environmental impact. ► The need for sustainable intensification can be reduced my managing demand and reducing food waste.